Iterative Learning Control for Switched Systems in the Presence of Input Saturation⁎This work is supported in part by the Russian Foundation for Basic Research under grant No. 19-08-00528_a and in part by National Science Centre in Poland, grant No. 2017/27/B/ST7/01874. Issue 2 (2020) - Pakshin, Pavel; Emelianova, Julia; Rogers, Eric; Galkowski, Krzysztof
Abstract: The paper considers iterative learning control for differential and discrete switched linear systems with control input saturation. A new design is developed based on the use of common vector Lyapunov functions. An example demonstrating the features and advantages of the new design is given.